Psychosocial dental impact in adult orthodontic patients: what about health competence? - María José González; Martín Romero; Cecilia Peñacoba (Health and Quality of Life Outcomes, 2019)
Abstract Background Several studies have assessed the psychological benefits of orthodontic treatment; however, the impact of competence on psychological benefits remains unknown. Aims: To analyze the change of the perception of psychosocial dental impact in a sample of adults undergoing orthodontic treatment (mild/moderate dental malocclusions) and to assess the possible moderating effect of health competence level. Methods A longitudinal prospective design was used. Three time points were included: baseline (T0), 6 months after starting orthodontic treatment (T1) and once treatment had finished (T2). The pretreatment sample consisted of 78 patients recruited from the Rey Juan Carlos University Dental Clinic, all of whom had moderate malocclusions and were going to undergo orthodontic treatment for approximately 18 months with fixed metal multibrackets. All participants were instructed to complete the Spanish version of the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) and the aesthetic component of the Index of Orthodontic Treatment Need (IOTN-AC) on the three points of the research. Statistical analysis involved the General Linear Model (GLM) repeated-measures ANOVA to test if the outcome measures of psychosocial dental impact significantly changed over time during orthodontic treatment (baseline, at 6-month evaluation and posttreatment). To assess the effect of the previous health competence levels (high/low) in the change from baseline to the 6-month assessment, for each PIDAQ dimension, a 2*2 (time*group) repeated measures ANOVA was performed. Results A significant increase was observed in dental self-confidence values (T0-T1 and T0-T2). Similar results were observed for the psychological impact variables and for the IOTN-AC scores, which showed significant decreases between T0 and T1 and between T0 and T2. Finally, significantly decreases were observed between T0 and T2 in aesthetic concern. Interaction effects were found regarding the health competence variable from T0-T1 for the psychological impact, social impact and aesthetic concern and the IOTN-AC index, with significant development results regarding the high competence group. Conclusions The first 6 months of orthodontic treatment seemed to be key to the development of psychosocial dental impact perception, during which the role of health competence was of great importance to developing a positive change. It is necessary to follow a biopsychosocial approach towards orthodontic treatment.